Transformasi Kepemimpinan Kepala Sekolah di Era Digital: Tinjauan Literatur tentang Tantangan dan Strategi Inovatif - Ivon Mukaddamah (Hikamatzu | Journal of Multidisciplinary, 2025)
This literature review explores the transformation of school leadership in the digital era by examining the challenges and innovative strategies faced by principals. The rapid advancement of technology has reshaped the educational landscape, requiring principals to evolve from traditional administrative roles into visionary leaders who integrate digital tools in school management, teaching, and human resource development. The findings highlight key challenges such as digital competence gaps, resistance to change, and limited infrastructure. In response, innovative leadership strategiesincluding data-driven decision making, strengthening digital literacy, fostering digital collaboration, and building an adaptive school cultureare essential to ensure effective and future-oriented school leadership in the 21st century